NEW DATA ON THE THREATENED Cerradomys goytaca (RODENTIA, CRICETIDAE) - Brandão, Marcus Vinicius; Felipe Rosa, Beatris; Fegies, Ana Claudia [UNESP]; Cristina Da Silva Belentani, Sonia (Universidad Nacional de Colombia, 2022)
Cerradomys goytaca is a cricetid rodent endemic to “Restinga” formations from southeastern Atlantic Forest. It is known from only five localities, and it is considered endangered of extinction. Herein, we furnish new data on C. goytaca from an additional locality in Rio de Janeiro state. The present record provides new data on habitat and represents the westernmost geographic limit of this poorly known species.
Nuevos datos sobre el amenazado Cerradomys goytaca (RODENTIA, CRICETIDAE)
Keywords: New record; Oryzomyini; Restinga-Rice-Rat; Sigmodontinae